The contribution of nursing expertise to the management of complex comorbidities in internal medicine setting: a systematic review - Alresheedi, Hend A.; Alanazi, Norah A.; Alshammari, Mariam H.; Alotaibi, Khulud M.; Al Wagdani, Abeer O.; Alotaibi, Najla H.; Alotibi, Amal M.; Al Rashidi, Hind M.; Eid, Nourah K.; Alshahrani, Shuruq N. (International Journal Of Community Medicine And Public Health, 2023)
The burden of comorbidities is on the rise, and nursing has long been recognized as having a crucial role in assisting individuals to manage long-term conditions. Over the past ten years, a growing number of chronic disease delivery models have given nurses great opportunities to develop roles and abilities focused on effective chronic disease management. We have conducted both electronic and manual searches within the potential databases to find relevant studies. Studies from the years 2010-2023 were included. Case reports with limited sample sizes, no descriptive statistics, review papers, and meta-analyses were excluded from this review. A quality assessment for all included studies was performed. Final inclusion resulted in a total of eight studies. Cardiovascular diseases, hypertension, and diabetes were the comorbidities reported by the majority of the studies, while chronic obstructive pulmonary disease, end-stage renal disease, and metastatic cancer were reported by each study. Overall, the findings suggest that nurses play a significant role in the management of comorbidities among patients, further improving patient outcomes, reducing readmissions and hospital costs, and preventing complications. The care of patients with complicated medical and social needs is coordinated through the employment of a wide range of interventions in an internal medicine setting. Nurse-led interventions /programs can play a vital part in reducing the burden of rising comorbidities among patients. However, the role of nurses in the internal medicine setting needs to be highlighted further by evidence-based research.